MORPHOFUNCTIONAL STATE OF THE TISSUES OF THE ORAL CAVITY WHEN USING NON-REMOVABLE ORTHOPEDIC STRUCTURES - Gubaev Muxiddin Sarimsakovich (Journals Park Publishing, 2022)
The article deals with the influence of fixed orthopedic structures on the state of oral tissues. The issues of modern methods of prosthetics based on implants are covered. An analysis was made of the most common errors and complications in prosthetics using fixed structures. The evaluation of the physical and technical properties of metal-ceramic structures remains poorly studied. To avoid chipping of ceramics, antagonistic prostheses are not brought to contact, which can lead to deformation. Thus, the question of the influence of fixed dentures on the clinical and morphological state in the absence of periodontal tissues remains unexplored.
Keywords: ceramic-metal, fixed dentures, periodontium, prosthetics, implants.